Simple rules : how to thrive in a complex world - Sull, Donald N. (Donald Norman); Eisenhardt, Kathleen M. (Houghton Mifflin Harcourt, 2015)
Outlines an approach to high-performance problem solving and decision making that draws on insights from survival guides, pop culture, and other sources.